2006
DOI: 10.1002/pola.21548
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of azobenzene‐containing poly(1‐alkyne)s with different functional pendant groups

Abstract: Abstract1‐Alkynes containing azobenzene mesogenic moieties [HCC(CH2)9O phNNphOR; R = ethyl (1), octyl (2), decyl (3), (S)‐2‐methylbutyl (4), or (S)‐1‐ethoxy‐1‐oxopropan‐2‐yl (5); ph = 1,4‐phenyl] were synthesized and polymerized in the presence of a Rh catalyst {(nbd)Rh+[B(C6H5)4]−; nbd = 2,5‐norbornadiene} to yield a series of liquid‐crystalline polymers in high yields (e.g., >75%). These polymers had moderate molecular weights (number‐average molecular weight ≥ 12,000), high cis contents in the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The polythiophene family is well known for its environmental stability, melt and solution processability, and versatile synthesis, which allow us to have a significant control over optical and electronic properties [11]. Conjugated polymers with liquid-crystalline (LC) groups in their side chains are currently drawing interest from the viewpoint of multifunctional electrical and optical materials [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In side chain type of LC-conjugated polymer, the main chain can be aligned by virtue of spontaneous orientation of the LC side chain.…”
Section: Introductionmentioning
confidence: 99%
“…The polythiophene family is well known for its environmental stability, melt and solution processability, and versatile synthesis, which allow us to have a significant control over optical and electronic properties [11]. Conjugated polymers with liquid-crystalline (LC) groups in their side chains are currently drawing interest from the viewpoint of multifunctional electrical and optical materials [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In side chain type of LC-conjugated polymer, the main chain can be aligned by virtue of spontaneous orientation of the LC side chain.…”
Section: Introductionmentioning
confidence: 99%
“…Attracted by the application perspective, recently, a variety of SCLCCP based on different conjugated main chain have been prepared, such as polyacetylenes, polythiophenes, and polyphenylenes, which can be endowed with such functional properties as mesomorphism, luminescence, photoconductivity, gas permeability, chain helicity 6–19. Tang and coworkers have synthesized a series of polyacetylenes bearing light‐emitting chromophore with different functional bridges and spacer length, such as {[CHC(CmH 2 m + 1 )‐OCO‐biphenyl‐OCO(CH 2 ) 10 CH 3 ]},20 {[ArCC(CH 2 ) m O‐biphenyl‐O(CH 2 ) 6 CH 3 ]}21 and {[ArCC(CH 2 ) m O‐Naphthyl]},22 which found that the light‐emitting chromophore endows the polymer with high luminescence, and the longer spacers favor the strong light emitting as well as better packing arrangement of the mesogens.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the assignment of this signal to a particular main chain configuration was not unequivocal. For poly(1‐alkyne)s prepared with Rh homogeneous catalysts,25, 37, 38 the 5.9 ppm signal was mostly assigned to the main‐chain olefinic proton on double bonds with cis configuration. This assignment came from the cis ‐transoidal stereoselectivity of Rh‐based catalysts, which was well proved in the case of polymerization of phenylacetylene type monomers 39.…”
Section: Resultsmentioning
confidence: 99%